Antimycobacterial Effect of Selenium Nanoparticles on Mycobacterium tuberculosis - Estevez, Hector; Palacios, Ainhoa; Gil, David; Anguita, Juan; Vallet-Regi, Maria; González, Blanca; Prados-Rosales, Rafael; Luque-Garcia, Jose L. (Frontiers in Microbiology, 2020)
Tuberculosis remains the leading cause of death from infection worldwide. In recent years, the occurrence of tuberculosis cases caused by drug-resistant strains has spread, and is expected to continue to grow. Therefore, the development of new alternative treatments to the use of antibiotics is highly important. In that sense, nanotechnology can play a very relevant role, due to the unique characteristics of nanoparticles. In fact, different types of nanoparticles have already been evaluated both as potential bactericides and as efficient drug delivery vehicles. In this work, the use of selenium nanoparticles has been evaluated to inhibit the growth of two types of mycobacteria: Mycobacterium smegmatis and Mycobacterium tuberculosis. The results showed that selenium nanoparticles stabilized with chitosan are able to inhibit the growth of both types of mycobacteria by damaging their cell envelope integrity. These results open a new opportunity for the use of this type of nanoparticles as antimycobacterial agents by themselves, or for the development of novel nanosystems that combine the action of these nanoparticles with other drugs.